2022
DOI: 10.21037/atm-22-1273
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune-related biomarkers in embryos with neural tube defects via a bioinformatics analysis

Abstract: Background Neural tube defects (NTDs) are one of the most common types of birth defects. Oral folic acid (FA) prophylaxis is currently available, but the pathogenesis of NTDs is not fully understood. We conducted this study to examine the role of the immune landscape of NTDs and identify novel diagnostic and therapeutic biomarkers. Methods We downloaded the GSE33111 data set of 12 NTD embryos and 12 healthy embryos in the same period of fetal development from the Gene E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Most of the neural axis anomalies occur in the caudal spinal or cranial areas [2,3]. With an incidence of 0.1% in the Western world and 1.86% worldwide, there are approximately 300,000 cases of NTDs that occur annually [4][5][6], with 88,000 deaths occurring per year worldwide [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the neural axis anomalies occur in the caudal spinal or cranial areas [2,3]. With an incidence of 0.1% in the Western world and 1.86% worldwide, there are approximately 300,000 cases of NTDs that occur annually [4][5][6], with 88,000 deaths occurring per year worldwide [7].…”
Section: Introductionmentioning
confidence: 99%
“…Genetics and environmental factors have significant contributing roles in the etiology of NTDs [2,4,5,7,8]. Genetics is implicated as a causative factor in 20% of the cases, whereas the nongenetic elements account for 80% of NTD incidence [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged neuroinflammation is believed to be associated with many neurological disorders, including Parkinson's disease [8], Alzheimer's disease [9], and multiple sclerosis [10]. A recent study has identified a series of immune-related genes in human NTDs [11]. Similarly, upregulated inflammation-related processes were found in spinal cords from rats with NTDs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Current diagnostic modalities, such as maternal serum alpha-fetoprotein screening, fetal ultrasonography, and amniocentesis, have limitations in terms of sensitivity, specificity, and invasiveness [21][22][23]. A recent study has identified immune-related genes as diagnostic biomarkers of NTDs in fetal tissues [11]. However, these biomarkers lack practical application because the detection of fetal tissue during pregnancy is challenging and carries risks.…”
Section: Introductionmentioning
confidence: 99%